2012
DOI: 10.1016/j.respe.2012.06.202
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and metabolic syndrome in Tunisian women

Abstract: Objectives. This study aimed to evaluate the effect of menopausal status on the risk of metabolic syndrome (MetS) in Tunisian women. Methods. We analyzed a total of 2680 women aged between 35 and 70 years. Blood pressure, anthropometric indices, fasting glucose, and lipid profile were measured. The MetS was assessed by the modified NCEP-ATPIII definition. Results. The mean values of waist circumference, blood pressure, plasma lipids, and fasting glucose were significantly higher in postmenopausal than in preme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
1
0
1
Order By: Relevance
“…In our study, according to the NCEP-ATP III definition, the frequency of post-menopausal women with metabolic syndrome (74.18%) was higher than that of peri-menopausal women (50.62%). This result is consistent with other results reported in studies from Thailand [37], Tunisia [38], and Brazil [39]. The study of Ebrahimpour et al [40] revealed that the frequency of metabolic syndrome in women differs according to their menopausal status; it is significantly higher in post-menopausal women [40], which is also consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, according to the NCEP-ATP III definition, the frequency of post-menopausal women with metabolic syndrome (74.18%) was higher than that of peri-menopausal women (50.62%). This result is consistent with other results reported in studies from Thailand [37], Tunisia [38], and Brazil [39]. The study of Ebrahimpour et al [40] revealed that the frequency of metabolic syndrome in women differs according to their menopausal status; it is significantly higher in post-menopausal women [40], which is also consistent with our results.…”
Section: Discussionsupporting
confidence: 93%
“…Notably, alterations in gonadal hormones levels represent important risk factors, highly correlated with MetS . Men with low plasma testosterone level have a consistent increase in the CVD risk and women, the incidence of MetS increases after the onset of menopause , because of the decline of plasma oestrogen levels and a relative increase in sex hormone binding globulin (SHBG) and testosterone levels. However, testosterone deficiency can be considered an important marker for CVD and mortality in men, but not in women.…”
Section: Introductionmentioning
confidence: 99%
“…Πράγματι, οι εμμηνοπαυσιακές γυναίκες φυσιολογικού σωματικού βάρους, που συμμετείχαν στη μελέτη, και είχαν υψηλό λόγο περιφέρειας μέσης προς περιφέρεια ισχίων, χαρακτηρίζονταν από υψηλότερο πάχος έσω χιτώνα καρωτίδων, κατά 10,5%, σε σύγκριση με τις νορμοβαρείς εμμηνοπαυσιακές γυναίκες φυσιολογικού λόγου μέσης/ισχίων. Η πλειονότητα των υπάρχουσων μελετών(Ben Ali et al 2014, Jouyandeh et al 2013, Pu et al 2017) αναφέρουν αύξηση του κινδύνου εμφάνισης μεταβολικού συνδρόμου κατά την εμμηνόπαυση, γεγονός που ενισχύει την αθηροσκληρυντική διαδικασία.…”
unclassified